Respuesta :

Answer:

x = [tex]\frac{23}{2}[/tex]

Step-by-step explanation:

Given

[tex]\frac{1}{6}[/tex](x - 5) = [tex]\frac{1}{2}[/tex](x + 6) ← multiply both sides by 6 to clear the fractions

x - 5 = 3(x + 6) ← distribute

x - 5 = 3x + 18 ( subtract x from both sides )

- 5 = 2x + 18 ( subtract 18 from both sides )

- 23 = 2x ( divide both sides by 2 )

- [tex]\frac{23}{2}[/tex] = x

Answer:

x= 11.5

Step-by-step explanation:

Hi!  Your gonna wanna start with the distributive property like this:

Take 1/6 and distribute it through x-5.

You end up with 1/6x-5/6

Do the same with the other side.

1/2x+6/2 = 1/2x+3

So now you have simplified to:

1/6x-5/6 = 1/2x+3

Add -5/6 to the other side

1/6x = 1/2x + 23/6

Subtract 1/2x

-1/3x = 23/6

Divide by negative 1/3 pn both sides

x = -69/6

x = 11.5 or 23/2 or 11 1/2

ACCESS MORE